Tomographic X‐ray scattering based on invariant reconstruction: analysis of the 3D nanostructure of bovine bone. Issue 2 (3rd March 2021) - De Falco, Paolino; Weinkamer, Richard; Wagermaier, Wolfgang; Li, Chenghao; Snow, Tim; Terrill, Nicholas J.; Gupta, Himadri S.; Goyal, Pawan; Stoll, Martin; Benner, Peter; Fratzl, Peter
Abstract : A new tomographic approach using X‐ray scattering is presented, allowing the characterization of the 3D nanostructure of hybrid materials. Abstract : Small‐angle X‐ray scattering (SAXS) is an effective characterization technique for multi‐phase nanocomposites. The structural complexity and heterogeneity of biological materials require the development of new techniques for the 3D characterization of their hierarchical structures. Emerging SAXS tomographic methods allow reconstruction of the 3D scattering pattern in each voxel but are costly in terms of synchrotron measurement time and computer time. To address this problem, an approach has been developed based on the reconstruction of SAXS invariants to allow for fast 3D characterization of nanostructured inhomogeneous materials. SAXS invariants are scalars replacing the 3D scattering patterns in each voxel, thus simplifying the 6D reconstruction problem to several 3D ones. Standard procedures for tomographic reconstruction can be directly adapted for this problem. The procedure is demonstrated by determining the distribution of the nanometric bone mineral particle thickness ( T parameter) throughout a macroscopic 3D volume of bovine cortical bone. The T parameter maps display spatial patterns of particle thickness in fibrolamellar bone units. Spatial correlation between the mineral nanostructure and microscopic features reveals that the mineral particles are particularly thin in the vicinity of vascular channels.